"Borders made in Great Britain": in conversation with Reza Amirkhani about his Afghanistan travelogue, Janistan, Kabulistan. Issue 1 (2nd January 2019) - Nazari, Hossein
ABSTRACT: Reza Amirkhani is a prominent Iranian novelist, travel writer, and cultural critic. He has won many literary awards in Iran and some of his works have been bestsellers. In this interview, Amirkhani discusses his journey to Afghanistan, which he undertook after the 2009 Iranian presidential election, and published as Janistan, Kabulistan in 2010. The travelogue begins with an account of the writer's ascent to Iran's Mount Damavand to escape politics, only to find that the political is inescapable, and closes with a discussion of elections in Iraq and Lebanon. Between the book's prelude and epilogue, in his signature style, Amirkhani weaves a narrative of his journey, which is interlaced with social, political, and cultural commentary on different aspects of Afghan (and sometimes Iranian) society. Drawing on a rich culture and history, Amirkhani offers insights into a country that is often represented stereotypically and produces a narrative that challenges much of the conventional wisdom on Afghanistan.